Design, expression, and evaluation of novel multiepitope chimeric antigen of Wuchereria bancrofti for the diagnosis of lymphatic filariasis - A structure-based strategy - Yasin, Nazeer; Laxmanappa, Hoti Sugerappa; Muddapur, Uday M.; Cheruvathur, Jennifer; Prakash, S. M. Uday; Thulasiram, Hirekodathakallu Venkataramaiah (International Immunopharmacology, 2020)
The Global Program for Elimination Lymphatic Filariasis (GPELF) is in an advanced stage and requires tools for diagnosing infection, assessing transmission and certification. This study was aimed at developing an antibody-based assay using a chiemric antigen containing multi-B-cell epitopes from antigens highly expressed in different stages of Wuchereria bancrofti to detect LF infection and its transmission. The antigen was express cloned and two indirect ELISA based (IgG1 & IgG4 based) antibody assays were developed using the recombinant antigen. The chimeric antigen displayed 1 and 3-fold reactivity with IgG1 and IgG4 antibodies, respectively in microfilaraial (mf) positive sera when compared to that in sera samples of Non-endemic normal sera (NEN) (O.D, 0.13 +/- 0.20 and 0.18 +/- 0.07), thus differentiating infected from uninfected individuals. In IgG1 and IgG4 antibody assays, the multiepitope antigen also showed reactivity (O.D, 0.27 +/- 0.18 and 0.16 +/- 0.03) in a small proportion (18 and 30, respectively out of 156) endemic normal individuals and in IgG1 antibody in a few (4) chronic patients (CP). The antigen did not react with IgG1 or IgG4 antibodies in the sera samples of malaria, scrub typhus, dengue, hookworm, and roundworm helminth cases (0.139 +/- 0.018, 0.144 +/- 0.007 0.17804 +/- 0.007 and 0.162 +/- 0.006), thus showing its high specificity. The sensitivity (%) and specificity (%) of the multi-epitope antigen-based IgG1 and IgG4 antibody assays are 100, 98.1 and 100, 99.52, respectively. Thus, the recombinant multiepitope antigen appears to have good potential in detecting active LF infection and in assessing its transmission in endemic communities.
Keywords: Filariasis; Multi-epitope antigen; Serodiagnosis; Transmission

Structural, molecular, functional and immunological characterization of Wuchereria bancrofti-galectin - Yasin, Nazeer; Laxmanappa, Hoti Sugerappa; Muddapur, Uday M.; Cheruvathur, Jennifer; Prakash, S. M. Udaya; Thulasiram, Hirekodathakallu Venkataramaiah (International Journal of Biological Macromolecules, 2020)
Galectins regulate growth and differentiation of immune cells and inflammation through their carbohydrate-binding function in humans, while also play a role in parasite survival. This study focused on the galectin of lymphatic filarial parasite Wuchereria bancrofti (Wb-Gal). The multiple sequence alignment with other galectins showed that the Wb-Gal belonged to galactoside binding lectin family, particularly tandem repeat type galectin-9. A homology model of Wb-Gal was developed in the I-TASser server using high similarity 3D structures with a quality score of 89.5. Molecular docking and dynamics studies revealed that the CCRD and NCRD of Wb-Gal bind with galactose and lactose. Further, Wb-Gal was cloned into the pET28 vector, expressed in E. coli Rosetta strain and purified by affinity chromatography. In the hemagglutination assays, the rWb-Gal bound to lactose, galactose, and glucose. Indirect Enzyme-Linked Immunosorbent Assay (ELISA) using different clinical filarial sera showed that the IgG and IgM response was against Wb-Gal x very high in all filarial clinical groups, whereas the IgA and IgG2 response was minimum to negligible. There was an enhanced response of IgG1 and IgG4 antibodies in Microfilaremics (MF) cases compared to Chronic Pathology (CP) and Endemic Normal (EN) individuals. Interestingly, the IgE response was comparatively higher in EN than MF and CP. These studies show that Wb-Gal is a member of the lectin family of proteins binding to different carbohydrates and may have an important role in the pathophysiology of filarial infection which needs to be investigated in greater detail. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Filariasis; Hemagglutination assay; Immunomodulation; Wuchereria bancrofti galectin